Ecology, behaviour and population dynamics of the Hartmann zebra Equus Zebra Hartmannae Matschie, 1898 in South West Africa - Eloff, F.C. (University of Pretoria, 2022)
Thesis (DSc (Wildlife Management))--University of Pretoria, 1971.